A discussion of the Canaanite mythological background to the Israelite concept of eschatological hope in Isaiah 24-27 - Steiner, E (2013)
The thesis begins with an overview of views concerning the dating of Isa 24–27 and its place within the genres of apocalyptic and eschatology, before stating its aim as showing how Canaanite myths were used by the author to give future hope rooted in cultic ideals. The second chapter looks at the image of the divine warrior, with particular emphasis on the chaos enemy as the dragon/serpent/sea, and the remarkable similarities between Isa 27:1 and the Ugaritic KTU 1.5.i.1–5. A possible cultic setting of the combat myth is examined, together with the question of why the myth appears here in an eschatological manner. The following chapter discusses the Israelite and Canaanite traditions concerning the holy mountain and divine banquet. Zion motifs are compared with those of Mt. Zaphon, and the nature of cultic feasts considered in Israelite and Canaanite literature, as well as later traditions. Chapter Four argues that the verses concerning death and resurrection represented exile/oppression and restoration, at a time when ideas of resurrection and judgment after death were emerging. The Israelite imagery of Mot/Death and Sheol are examined in relation to the nature of Ugaritic Mot, showing how Canaanite traditions were used to demonstrate Yahweh’s might and the possibility of individual and universal restoration. The following chapter places Israelite religion within the context of Canaanite fertility cults and popular practices. That myth and cult are connected is the basis for the view that the themes in Isa 24–27 were passed down to the post-exilic era via cultic activities and the reuse of myths to promote Yahweh, whether the author was aware that he was using ancient, mythological ideas or not. The sixth chapter gives a short overview of hope in the Hebrew Bible, before demonstrating how the universalism of Isa 24–27 combines with the ancient mythic themes to provide an eschatological hope in an all-encompassing deity. The paper concludes that the author of these chapters deliberately used Canaanite mythology to show how the final victory, rule, and celebration of Yahweh would bring about a personal and moral victory for all nations.